Quality of Life in ESRD Patients - Faseeh K M; Harshavardhan R (Medical Science: Trends and Innovations Vol. 10, 2025)
Background and Aim: Assessment of health-related quality of life in end-stage renal disease (ESRD) patients. The quality of life of the patients may be greatly reduced because it necessitates lifelong treatment in the form of renal replacement therapy. Therefore, the main goal of the study is to evaluate the QOL (quality of life) of patients receiving hemodialysis using WHO-QOL criteria. Methods: At the Dr. B.R. AMCH dialysis unit, a cross-sectional descriptive study involving (n=134) patients (of whom 34 gave negative consent) was carried out over the course of three years, from September 10, 2018, to September 10, 2021. Results: A total of 100 CKD patients participated in the study, which included 60 males and 39 females and 1 preferred not to say, visiting DR. B.R. AMCH, being treated on OUT patient basis. The quality of life was assessed based on WHOQOL questionnaire, assuming each measurement had same Weightage. The study conducted showed the quality of life was poor and very poor (51%), with neither good nor bad as 22% and only 25% as good. Conclusion: WHO QOL is a trustworthy tool for assessing QOL in ESRD patients. The research indicates that the progression of the illness has a negative impact on both mental and physical health, as well as causing financial strain and strained relationships with others.